Optimization of Heat and Mass Exchange - Agnew, Brian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of Processes operates on the basis of a rigorous peer-review with a single-blind assessment and at least two independent reviewers, thereby ensuring a high quality final product. I would like to thank our reviewers, for providing the authors with constructive comments, and Editorial Board, for their professional advice that led to the final decision. I am sure that, in coming years, readers of this Special Issue will find the scientific manuscripts interesting and beneficial to their research.